HUBUNGAN POLA ASUH TERHADAP STATUS GIZI PADA ANAK TK DI KOTA YOGYAKARTA - Reynaldy Valentino Pratama Marpaung; Yoseph Leonardo Samodra; Slamet Sunarno Harjosuwarno (Jurnal Ilmiah Kesehatan Media Husada, 2021)
Nutritional status have important impact with growth and development children in pre primary school. Undernutrition in children have a relationship between impaired growth and physical development. Meanwhile, overnutrition with a severe degree will causes respiratory problem, hypertension and dermatitis. Therefore needed to analyze a suspected condition that affect nutritional status like parenting. The objective of this research to find out the relationship between parenting toward nutritional status of preschool children in Yogyakarta. This research used an observational analytic with a cross sectional design. The population in this study were all students from Bopkri Gondokusuman, Bopkri Ungaran and Bina Putra Preschool and their mothers, totalling 50 samples. Nutritional status is determined by measuring the children body weight and height, the categorize them with the BMI/Age base on CDC growth chart 2000. Parenting are measured by a questionnaire. Research result based on the fisher’s exact test, there is no significant relationship between parenting (p = ,0590), nutritional fulfillment (p = 0,140), basic health care (p=1,000) toward nutritional status of children. Therefore, it can be conclude that there is no significant relationship between parenting toward the nutritional status of preschool children in Yogyakarta.